Some Extensions Of Log Aesthetic Curves And Its Acceleration Using General Processing Unit (GPU) - Teh, Yee Meng (2022)
The first part investigates the characteristics of Log Aesthetic Curve (LAC). The second part proposes new techniques to accelerate the computation of line of curvature (LoC) by using General Processing Unit (GPU) and the last part is to implement the LACs to the surface equations.